Foraging choices of vampire bats in diverse landscapes: potential implications for land‐use change and disease transmission. Issue 4 (26th May 2016) - Streicker, Daniel G.; Allgeier, Jacob E.
Summary: In Latin America, the common vampire bat Desmodus rotundus is the primary reservoir of rabies, a zoonotic virus that kills thousands of livestock annually and causes sporadic and lethal human rabies outbreaks. The proliferation of livestock provides an abundant food resource for this obligate blood‐feeding species that could alter its foraging behaviour and rabies transmission, but poor understanding of the dietary plasticity of vampire bats limits understanding of how livestock influences rabies risk. We analysed individual‐ and population‐level foraging behaviour by applying δ 13 C and δ 15 N stable isotope analysis to hair samples from 183 vampire bats captured from nine colonies in Peru. We also assessed the isotopic distributions of realized prey by analysing blood meals extracted from engorged bats and samples collected from potential prey species. In two adjacent but contrasting areas of the Amazon with scarce and abundant livestock, we used questionnaires to evaluate the incidence of feeding on humans. Population‐level isotopic signatures suggested substantial among‐site variation in feeding behaviour, including reliance on livestock in some colonies and feeding on combinations of domestic and wild prey in others. Isotopic heterogeneity within bat colonies was among the largest recorded in vertebrate populations, indicating that individuals consistently fed on distinct prey resources and across distinct trophic levels. In some sites, isotopic values of realized prey spanned broad ranges, suggesting that bats with intermediate isotopic values could plausibly be dietary specialists rather than generalists. Bayesian estimates of isotopic niche width varied up to ninefold among colonies and were maximized where wildlife and livestock were present at low levels, but declined with greater availability of livestock. In the Amazon, the absence of livestock was associated with feeding on humans and wildlife. Policy implications . We provide the first insights into the foraging behaviour of vampire bats in habitats with common depredation on humans and show how vampire bat foraging may respond to land‐use change. Our results demonstrate risks of rabies transmission from bats to other wildlife and are consistent with the hypothesis that introducing livestock might reduce the burden of human rabies in high‐risk communities.